The impact of cloud computing on the development of the effectiveness and efficiency of accounting information systems A study of the opinions of a sample of faculty members, and professionals from academics, in Libya - اسميو إسماعيل المهدي محمد (Scientific Journal of University of Benghazi, 2022)
This study aims to find out the impact of cloud computing on the development of the effectiveness and efficiency of accounting information systems, which is "a general concept that includes a new type of infrastructure, and software, which is provided by the system that stores information or applications on the Internet in a way that allows the user to access them from any computer." (Misikh, 2018, p. 11), where the hypotheses of the study were tested on (102) random samples, to include the opinions of different functional segments of faculty members in Libyan universities, and professionals (accountants and auditors) who practice this profession from faculty members, where data was collected for this study using a questionnaire form. The researcher concluded through the statistical results that dealing with electronic systems leads to ease of performance and reducing time, cloud-computing technology contributes to increasing the efficiency of the performance of institutions. The uses of cloud computing applications also affect the effectiveness of providing accounting information. The use of cloud computing technology in the field of accounting is important to keep pace with contemporary technological developments. Reducing the large building space for the size of institutions by reducing the size and number of offices because they allow access anywhere without the commitment of management to a specific place. Cloud computing as a core technology is becoming more important with big data, as it provides a significant increase in productivity and cost-effectiveness for businesses.